Exonic STK11 deletions are not a rare cause of Peutz-Jeghers syndrome. Issue 4 (31st March 2006) - Hearle, N C M; Rudd, M F; Lim, W; Murday, V; Lim, A G; Phillips, R K; Lee, P W; O'Donohue, J; Morrison, P J; Norman, A; Hodgson, S V; Lucassen, A; et al.
Abstract : Background: Peutz-Jeghers syndrome (PJS) is a rare, autosomal dominant cancer predisposition syndrome characterised by oro-facial pigmentation and hamartomatous polyposis of the gastrointestinal tract. A causal germline mutation in STK11 can be identified in 30% to 80% of PJS patients. Methods: Here we report the comprehensive mutational analysis of STK11 in 38 PJS probands applying conventional PCR based mutation detection methods and the recently introduced MLPA (multiplex ligation dependent probe amplification) technique developed for the identification of exonic deletions/duplications. Results: Nineteen of 38 probands (50%) had detectable point mutations or small scale deletions/insertions and six probands (16%) had genomic deletions encompassing one or more STK11 exons. Conclusions: These findings demonstrate that exonic STK11 deletions are a common cause of PJS and provide a strong rationale for conducting a primary screen for such mutations in patients.